MENINGKATKAN HASIL BELAJAR MELALUI PEMBELAJARAN NUMBER HEAD TOGETHER - Siti Aisyah; Vani Nurasyiah (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2018)
This study aims to determine the cognitive achievement of students before using cooperative learning model Numbered Heads Together (NHT) and to know the learning activities undertaken by teachers and students using the NHT model on science subjects. The research describing the picture of the process of learning science by using cooperative learning model NHT, and describe the cognitive learning outcomes of students after using NHT. The methodology in this research is the Classroom Action Research comprising the steps of planning, implementation, observation, and reflection that lasted for two cycles, with the subject of fifth-grade students of Islamic primary school Sirojul Subang district West Java Indonesia with 27 students, consisting of 13 girls and 14 boys. Based on the results of research analysis that the implementation of NHT model is well-implemented student cognitive learning outcomes in the first cycle obtained an average value of 76 with 74% learning completeness and in cycle II obtained an average value 91 with 100% complete learning. Thus there is a significant improvement in the learning process using cooperative learning model type Numbered Heads Together on science subjects.